Identifying Government's Role towards Developing Sustainable Strategies in Tourism Industry. - Radhika P.C. and Johney Johnson (Pacific Business Review International, 2017)
Now tourism has become one of the major economic activities of Kerala. The vast developments in this sector also results in different types negative impacts. The mitigation of these negative impacts is possible by the proactive role of government. The present study tries to explain the different role of government in this sector to ensure sustainable development. The study is based on both primary and secondary data. The primary data was collected from two samples. One sample is the foreign tourists and the second sample is the resident community. The data was collected from Fortcochi, Kumarakom and Munnar. Random sampling method was adopted for collecting data from resident community from the three destinations and a total of 300 data was collected. The convenience sampling method was adopted for collecting data from foreign tourist. The study found that the most important role of government as per the opinion of foreign tourist is as the infrastructure developer, which is followed by protector of tourism resources, human resource developer, Promoter of tourism, coordinator of all departments of tourism and formulator of tourism policies. As per the opinion of resident community, the government has got three important roles to play to ensure community support and they are as ‘Community Developer’, ‘Community Participation’ and as ‘the Controller of Tourism cost’.